The predictors of occupational disability in obsessive-compulsive disorder in a large clinical sample (Annals of Medical Research, 2021)
Aim: Obsessive-compulsive disorder (OCD) is a common mental disorder leading to severe loss of functioning. We aimed to investigate socio-demographic and clinical factors affecting occupational disability in OCD. Material and Methods: It is a cross sectional study with individuals recruited from an outpatient psychiatry clinic. A total of 393 patients were given the Yale-Brown Obsessive Compulsive Scale (Y-BOCS), Hamilton Depression Rating Scale-17 Item (HAM-D), Beck Anxiety Inventory, Barratt Impulseness Scale-11 and Wender Utah Rating Scale. Occupational disability was defined as the inability to work over the past month due to pychopathology associated with OCD. Housewives, students and retired people were excluded. Results: The rates of occupational disability were 52.9% in the whole sample, 44.3% in men and 60% in women. Higher Y-BOCS scores, higher HAM-D scores, being single, female gender, younger age at first treatment, less school years and previous suicide attempt were associated with a higher risk of occupational disability. The BAI scores, previous hospitalization, age at onset, smoking, childhood ADHD and past or present tic disorder did not statistically affect occupational status. Conclusions: OCD is associated with serious occupational disability causing inability to work in more than half of patients. The severity of OCD and depressive symptoms, marital status, gender, education level, age at first treatment and history of suicide attempt predict occupational disability. Keywords: Occupational disability; disability; functioning; obsessive-compulsive disorder; impulsivity; Attention Deficit and Hyperactivity Disorder (ADHD).
Keywords: Occupational disability; disability; functioning; obsessive-compulsive disorder; impulsivity; Attention Deficit and Hyperactivity Disorder (ADHD).